Preparation method of catalytic electrode and catalytic electrode
By forming a catalytic precursor layer on the surface of the conductive substrate and passing alkaline electrolyte and micro current into the electrolyte cell to generate a porous catalytic layer, the problem of low stability and activity of the catalytic electrode is solved, and high-efficiency and low-cost large-scale production is achieved, and the mechanical stability and activity of the electrode are improved.
Patent Information
- Application Number
- CN202510565538.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-07-01
AI Technical Summary
The existing catalytic electrode has poor stability and low activity, making it difficult to produce on a large scale, and precious metal catalysts are costly and unstable, and non-precious metal catalysts are prone to fall off under high current density. The existing preparation process has large energy consumption and waste emission problems.
An acid catalytic precursor solution is used to form a catalytic precursor layer on the surface of the conductive substrate. An alkaline electrolyte solution is passed into the prefabricated electrolyte cell for reaction, and a porous catalytic layer is formed in a directional manner. The nucleation growth additives and micro currents are used to promote the catalytic layer nucleation and growth, and a non-precious metal salt and the third component metal salt are combined to form a NiMxNy(O)OH catalytic layer.
It improves the stability and activity of the catalytic electrode, reduces the preparation cost and time, enhances the connection between the substrate and the catalytic layer, provides more active sites, and improves the service life and electrolytic efficiency of the electrode.
Smart Images

Figure CN120231076A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen production by electrolyzing water, and specifically relates to a preparation method of a catalytic electrode and a catalytic electrode. Background Art
[0002] At present, electrolyzing alkaline water to produce hydrogen has the advantages of high technology maturity and low investment in electrolyzers, and can be used for large-scale hydrogen production. The oxygen evolution electrode is a key material in the electrolyzer, and it is often based on a nickel substrate, such as nickel wire mesh and nickel foam. Such pure nickel electrodes have a small surface active area, slow catalytic reaction kinetics, and require a high electrolysis overpotential. Therefore, loading active nickel particles or nickel-based transition metal (Mn, Fe, Co, Cu, Mo) oxides, hydroxides, and noble metal oxide coatings on their surfaces are all recognized effective methods to improve the activity of nickel electrodes.
[0003] The oxygen evolution reaction (OER) is a four-electron transfer process with slow kinetics and requires a high overpotential, which causes the electrode material to be easily corroded, washed away, and peeled off in a strong oxidation environment, affecting stability. In order to improve the performance of the electrolyzed water oxygen evolution electrode, Patent CN104937142B discloses a method for preparing an Ir-containing noble metal anode by a thermal decomposition method, and Patent CN113802130A uses a hydrothermal method to prepare an Ir-Ru noble metal catalyst. This kind of noble metal anode has high activity, but is expensive and difficult to industrialize. Moreover, in an acidic medium, the catalyst electrode of noble metal is prone to unstable phenomena such as corrosion, dissolution, and reconstruction. The currently developed non-noble metal electrolyzed water catalysts mainly include transition metal alloys such as Fe, Co, Ni and their oxides, hydroxides, sulfides, phosphides and other catalyst materials with nanostructures. It is reported that such non-noble metal materials have high activity, but most of them are powder catalysts. A binder is used to combine metal nanoparticles with the carrier, and the force between them is weak. It is easy to fall off from the electrode surface during the violent reaction process at high current density, thus affecting the activity and stability of the electrode. Patent CN114774967A uses plasma spraying technology to deposit nickel-aluminum catalytic alloy powder on a substrate mesh and performs dealumination activation treatment in hot alkaline solution to obtain a porous nickel structure. This kind of electrode is simple to prepare, but its oxygen evolution activity is significantly lacking, and the electrode falls off significantly during long-term testing, with poor stability. In addition, Patent CN117488357A uses electrodeposition method to deposit active substances on the surface of nickel foam. This method is suitable for preparing different metal elements and is simple, but there is a large energy consumption in the preparation process, which is not conducive to large-scale production, and there are even problems of waste discharge. Therefore, developing new catalyst materials, optimizing the electrode preparation process, and improving the catalytic activity and stability of the electrode are of great significance for the efficiency problem in the electrolyzed water process, reducing the hydrogen production cost, and promoting the commercialization process of the electrolyzed water hydrogen production technology. Summary of the Invention
[0004] The object of the present invention is to provide a preparation method of a catalytic electrode and a catalytic electrode, so as to overcome the problems of poor stability, low activity, and difficulty in large-scale production of current catalytic electrodes.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] The present application provides a preparation method of a catalytic electrode, including:
[0007] Using an acidic catalytic precursor solution to form a catalytic precursor layer on the surface of a preset conductive substrate;
[0008] Loading the conductive substrate with the catalytic precursor layer into a prefabricated electrolytic cell;
[0009] Introducing an alkaline electrolyte containing an induced growth additive and a microcurrent into the prefabricated electrolytic cell for reaction and induced growth, so as to directionally generate a porous catalytic layer with flow channels on the conductive substrate with the catalytic precursor layer, and obtaining a catalytic electrode after thorough cleaning.
[0010] The catalytic precursor solution in the present invention contains a target non-noble metal salt and a third-component metal salt, and the target non-noble metal includes at least one of Mn, Fe, Co, Cu, and Mo; the third-component metal includes at least one of Zn, Cr, Ce, La, Pr, Nd, Sm, or Gd.
[0011] Further, the step of using an acidic catalytic precursor solution to form a catalytic precursor layer on the surface of a preset conductive substrate includes:
[0012] Uniformly coating the acidic catalytic precursor solution on the surface of the preset conductive substrate and performing a drying treatment; repeating this coating and drying treatment process multiple times until the weight of the catalytic precursor layer on the surface of the preset conductive substrate reaches a target value, and the minimum value of the target value is 0.2 mg / cm 2 .
[0013] The step of loading the conductive substrate with the catalytic precursor layer into a prefabricated electrolytic cell in the present invention includes: loading the conductive substrate with the catalytic precursor layer into the anode chamber of the prefabricated electrolytic cell.
[0014] Further, the prefabricated electrolytic cell includes a plurality of reaction chambers, each reaction chamber is composed of an anode chamber and a cathode chamber, the anode chamber contains an anode electrode, and the cathode chamber contains a cathode electrode
[0015] The alkaline electrolyte includes a KOH or NaOH electrolyte, with a concentration of 20%-30%, a temperature of 40-120 °C, the duration of introducing the alkaline electrolyte is 10 min-120 min, and the electrolyte flow rate per unit area is 30-100 mL / min.
[0016] The growth-inducing additive in the present invention is any one of 3,4,9,10-perylene tetracarboxylic dianhydride, 1,3,5-tris(1-phenyl-1H-benzoimidazol-2-yl)benzene, and purified terephthalic acid, and the addition amount is 0.01%-1%.
[0017] The current density of the microcurrent in the present invention is 0.02 - 20 mA / cm 2 , and the duration of passing the current is 10 min - 120 min.
[0018] In some embodiments of the present invention, the metal salt is one or more of nitrates, sulfates, chlorides, and acetates;
[0019] The cleaning in the present invention is to drain the alkali solution in the prefabricated electrolytic cell, and pass pure water to repeatedly clean the electrodes in the reaction chamber to obtain the catalytic electrode. In some embodiments of the present invention, the alkali solution does not change in terms of composition, concentration, etc. during the electrode preparation process, and can be recycled in the next batch of electrode preparation, improving the utilization rate of the reagent and reducing waste emissions.
[0020] In some embodiments of the present invention, before forming the catalytic precursor layer on the surface of the preset conductive substrate using the acidic catalytic precursor solution, it further includes:
[0021] Immersing the conductive substrate in an HCl solution for ultrasonic or sandblasting treatment;
[0022] Then, the ultrasonically or sandblasted conductive substrate is ultrasonically treated in deionized water or a mixed solution of deionized water and ethanol or acetone, and dried.
[0023] The present invention also provides a catalytic electrode prepared by the above-mentioned preparation method of the catalytic electrode. The catalytic layer of the catalytic electrode has a composition of NiMxNy(O)OH, where 0 < x < 5, 0 ≤ y < 5, M is at least one of Mn, Fe, Co, Cu, and Mo, and the third-component additive N is at least one of Zn, Cr, Ce, La, Pr, Nd, Sm, or Gd.
[0024] The conductive substrate in the present invention includes at least one of nickel and nickel-based alloys, such as nickel woven mesh, nickel foam, or perforated nickel plate mesh.
[0025] The present invention relates to the technical field of hydrogen production by electrolyzing water, and specifically discloses a preparation method of a catalytic electrode and a catalytic electrode. The method specifically includes forming a catalytic precursor layer on the surface of a preset conductive substrate by using an acidic catalytic precursor solution; loading the conductive substrate with the catalytic precursor layer into a prefabricated electrolytic cell; introducing an alkaline electrolyte containing an induced growth additive and a microcurrent into the prefabricated electrolytic cell for reaction and induced growth, so as to directionally generate a porous catalytic layer with an intrinsic flow channel formed by electrolyte circulation on the conductive substrate with the catalytic precursor layer. During the in-situ reaction process of the electrolytic cell, the additive is a growth inducer, which can reduce the reaction energy barrier, promote the nucleation growth of the catalytic layer, and accelerate the growth reaction rate of the catalytic layer. At the same time, a microcurrent is introduced for induction, local oxidation occurs in the interface region, the diffusion rate and migration rate of grain boundaries increase, and the catalytic layer grows upward on the substrate (i.e., the conductive substrate). In addition, the introduction of the microcurrent can effectively strengthen the connection between the substrate and the catalytic layer. The circulation of the electrolyte not only provides an alkaline environment for the growth of the catalytic layer, but also weakens the accumulation of the catalytic layer during the growth process of the catalytic layer, reduces the risk of the catalytic layer being washed off, provides a physical channel for the electrolyte circulation and gas analysis during the actual hydrogen production by electrolysis, increases the electrolysis specific surface area, is beneficial to the increase of electrode activity, and greatly improves the stability and service life of the catalytic layer. The use of the additive, the introduction of the microcurrent, and the electrolyte circulation all guarantee the rapid nucleation of the catalytic layer and reduce the post-treatment work after the preparation of the catalytic layer in the electrolytic cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention, and those of ordinary skill in the art can also obtain other drawings based on these drawings without creative efforts.
[0027] Figure 1 It is a schematic flowchart of the preparation method of the catalytic electrode provided by the embodiment of the present invention;
[0028] Figure 2 It is a schematic flowchart of the preparation method of the catalytic electrode provided by another embodiment of the present invention;
[0029] Figure 3 It is a schematic diagram of a replaceable electrolysis unit simple prefabricated electrolytic cell provided by the embodiment of the present invention;
[0030] Figure 4 It is a scanning electron microscope image of the NiFe anode prepared in-situ in the electrolytic cell by the preparation method of the catalytic electrode provided by the embodiment of the present invention;
[0031] Figure 5Scanning electron microscope image of the NiFe anode prepared outside the electrolytic cell based on the preparation method of the catalytic electrode provided in the embodiments of the present invention;
[0032] Figure 6 Scanning electron microscope image of the NiFe anode prepared by the preparation method of the catalytic electrode provided in the embodiments of the present invention and operated under the condition of 6 kA / m² for 500 h.
[0033] Figure 7 Comparison diagram of current-voltage relationships of different embodiments and comparative examples under the same test conditions;
[0034] Figure 8 Test diagram of the electrode stability of the electrode prepared by the preparation method of the catalytic electrode provided in an embodiment of the present invention. Detailed implementation manners
[0035] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions of the present invention will be described in detail below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other implementation manners obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope protected by the present invention.
[0036] Method embodiment:
[0037] Figure 1 It is a schematic flow chart of the preparation method of the catalytic electrode provided in the embodiments of the present invention. Please refer to Figure 1 , and this embodiment may include the following steps:
[0038] S101. Using an acidic catalytic precursor solution, form a catalytic precursor layer on the surface of a preset conductive substrate.
[0039] Specifically, in the present application, an acidic catalytic precursor solution can be prepared in advance. For example, a soluble salt can be dissolved in an acidic solvent to obtain the catalytic precursor solution. Then, the catalytic precursor solution is used to form a catalytic precursor layer on the surface of the preset conductive substrate.
[0040] For example, the catalytic precursor solution is coated on the surface of the conductive substrate. It can be understood that during the coating process, the acidic catalytic precursor solution will perform ion exchange with the surface of the conductive substrate to achieve the first reaction, thereby forming a stable catalytic precursor layer on the surface of the conductive substrate, and further strengthening the connection between the finally formed catalytic layer and the conductive substrate (the second reaction occurs between the alkaline electrolyte and the catalytic precursor layer).
[0041] S102. Load the conductive substrate with the catalytic precursor layer into a prefabricated electrolytic cell.
[0042] Specifically, according to the solutions in the prior art, a conductive substrate with a catalytic precursor layer can be loaded into a replaceable electrolysis unit in a simple electrolysis cell, such as an anodic chamber, to act as an oxygen evolution anode.
[0043] S103: Introduce a high-temperature alkaline electrolyte containing an induced growth additive and a microcurrent into the electrolysis cell for reaction and induced growth, so as to directionally generate a porous catalytic layer with flow channels on the conductive substrate with a catalytic precursor layer, and obtain a catalytic electrode.
[0044] Specifically, introduce an alkaline electrolyte, such as a high-temperature alkaline electrolyte, into the electrolysis cell, so that the alkaline electrolyte reacts with the catalytic precursor layer in a second reaction. The induced growth additive contained therein can accelerate the nucleation process of the catalytic layer by reducing the nucleation free energy. At the same time, introduce a microcurrent to perform induced growth through the microcurrent, so as to directionally generate a porous catalytic layer with flow channels on the conductive substrate with a catalytic precursor layer, and obtain a catalytic electrode. In this application, under the action of the introduced microcurrent, the electromigration effect makes the crystal grow along the direction with the minimum resistance. Therefore, when the alkaline electrolyte reacts with the catalytic precursor layer, a directional and stable porous catalytic active material layer, that is, a catalytic layer, is formed on the surface of the conductive substrate, and a catalytic electrode is obtained.
[0045] The preparation method of the catalytic electrode provided by the embodiment of the present invention first forms a catalytic precursor layer on the surface of a preset conductive substrate by using an acidic catalytic precursor solution; then loads the conductive substrate with the catalytic precursor layer into an electrolysis cell; finally, introduces an alkaline electrolyte containing an induced growth additive and a current into the electrolysis cell to generate a catalytic layer on the conductive substrate with the catalytic precursor layer, and obtain a catalytic electrode. In this way, because during the preparation, the electrode directly completes growth in the electrolysis cell, the costs and time for activation and cleaning of electrode preparation are greatly reduced, which is simple and efficient; moreover, the in-situ grown catalytic layer is connected to the conductive substrate by van der Waals forces, and has better stability than mechanical forces; at the same time, the directional growth induced by the additive and the microcurrent stimulates the interfacial reaction, can provide more active sites, is beneficial to electron and proton transport, and greatly improves the activity and service life of the catalytic electrode. In addition, on the basis of the above preparation method, a third component can be introduced as a catalytic reaction assistant to adjust the Lewis acid sites on the surface of the catalyst and enhance the structural stability, further improving the activity and life of the electrode.
[0046] In some embodiments of the present application, before forming the catalytic precursor layer on the surface of the preset conductive substrate by using the acidic catalytic precursor solution, pretreatment of the conductive substrate can also be included, which can include: immersing the conductive substrate in an HCl solution for ultrasonic treatment or sandblasting; then successively performing ultrasonic treatment on the conductive substrate after ultrasonic treatment or sandblasting in ethanol and acetone; finally, cleaning the conductive substrate after ultrasonic treatment in acetone with deionized water and drying.
[0047] For example, the conductive substrate is immersed in an HCl solution and ultrasonically or sandblasted to remove surface oxides; after being taken out, it is ultrasonically treated in ethanol and acetone respectively, and finally washed with deionized water and dried to obtain a treated conductive substrate such as a nickel mesh. In some embodiments, the concentration of the HCl solution can be 1-5 mol / L, the treatment temperature is 40-80°C, and the immersion time is 30-60 min.
[0048] Furthermore, in some embodiments, the conductive substrate can be any form of nickel and nickel alloys, for example, it can be any one of nickel mesh, nickel plate, nickel foam, nickel woven mesh, nickel stretched mesh, nickel perforated plate, nickel perforated mesh and nickel felt.
[0049] In some embodiments, the acidic catalytic precursor solution mentioned in the above embodiments may be a solution formed by dissolving one or more of the nitrates, sulfates, chlorides and acetates of the target non-precious metals in an acidic solvent (nitrates are preferably used); wherein the target non-precious metals include at least one of nickel, cobalt, iron, manganese and copper, and a third component may also be added, for example, at least one of zinc, chromium, cerium, lanthanum, praseodymium, neodymium, samarium and gadolinium (or their nitrates, sulfates, chlorides and acetates).
[0050] For example, in some embodiments, the catalytic precursor solution may be selected from one or more of nitrates, sulfates, chlorides, and acetates of non-precious metals such as nickel, cobalt, iron, manganese, copper, zinc, chromium, cerium, lanthanum, praseodymium, neodymium, samarium, and gadolinium, with a concentration of 0.01-5 mol / L. In other embodiments, the solvent of the catalytic precursor solution may be water or a mixed solvent of water and acid, wherein the acid is at least one of nitric acid, hydrochloric acid, sulfuric acid, and acetic acid, with a concentration of 0.01-5 mol / L.
[0051] After obtaining the catalytic precursor solution, in some embodiments of the present application, using the acidic catalytic precursor solution to form a catalytic precursor layer on the surface of a preset conductive substrate may include: uniformly coating the acidic catalytic precursor solution on the surface of the preset conductive substrate and performing a drying process; and sequentially repeating the coating and drying processes until the weight of the catalytic precursor layer on the surface of the preset conductive substrate reaches a target value, wherein the minimum value of the target value is 0.2 mg / cm 2 .
[0052] For example, in practical applications, the prepared catalytic precursor solution is evenly coated on the surface of the conductive substrate and dried. The coating method can be dipping, brushing, roller coating, spraying, etc.; and the drying temperature can be 40-120°C. After multiple sequential coating and drying treatments, the catalytic precursor layer loading on the conductive substrate is 0.2 mg / cm 2 above.
[0053] Based on the above embodiments, an in-situ growth step inside the prefabricated electrolytic cell is carried out, that is, the conductive substrate with the catalytic precursor layer is loaded into the anode chamber of the prefabricated electrolytic cell to act as the oxygen evolution anode; then an alkaline electrolyte and a weak current are continuously introduced into the electrolytic cell to carry out the in-situ growth reaction. Among them, the alkaline electrolyte is KOH or NaOH electrolyte, with a concentration of 20%-30%, preferably 30wt%, and the flow rate is 1-4 mL / min per unit electrode area; the temperature of in-situ growth is 40-120 °C, and the current density introduced at this place is 0.02-20 mA / cm 2 By introducing a weak current, the growth of the catalytic layer is induced, and finally an oxygen evolution electrode, that is, a catalytic electrode, is obtained.
[0054] Among them, the above-mentioned prefabricated electrolytic cell is a simple electrolytic cell with replaceable electrolytic units, such as Figure 3 shown, which consists of 1 - replaceable electrolytic unit, 2 - fixed end plate, 3 - movable end plate, 4 - fixed clamping plate, 5 - tightening spiral spring assembly. The replaceable electrolytic unit consists of positive and negative bipolar plates, anode electrodes, diaphragms, cathode electrodes, sealing washers, etc.
[0055] It should be noted that the catalytic electrode prepared by the preparation method of the catalytic electrode provided by the present application is composed of a conductive substrate made of nickel or nickel-based alloy and a catalytic layer loaded on the surface of the substrate. Finally, the composition of the catalytic layer includes: nickel-based hydroxide or hydroxyoxide or a mixture of hydroxide and hydroxyoxide, with the general formula NiM x N y (O)OH, 0 < x < 5, 0 ≤ y < 5. M is at least one of Mn, Fe, Co, Cu, Mo, and the third component N is one or several of zinc, chromium, cerium, praseodymium, neodymium, samarium, gadolinium.
[0056] In the preparation method provided by the present application, when a catalytic precursor solution containing non-precious metals, oxides and non-precious metals is coated on the surface of the conductive substrate of nickel or nickel-based alloy and dried and cured to form a catalytic precursor solution layer on the surface of the conductive substrate, when the catalytic precursor solution is acidic, nickel in the conductive substrate will exchange and precipitate with the metals in the acidic precursor solution to form a stable precursor solution layer on the surface of the conductive substrate. The precursor layer then reacts with the high-concentration alkaline electrolyte to generate a catalytic layer containing nickel-based hydroxide or hydroxyoxide or a mixture of hydroxide and hydroxyoxide on the surface of the conductive substrate, obtaining a catalytic electrode.
[0057] Among them, the catalytic layer is tightly combined with the conductive substrate, promoting the transport of electrons and protons and the penetration of the electrolyte, greatly improving the mechanical stability of the electrode. During the in-situ reaction process of the electrolytic cell, a growth inducer is added to lower the reaction energy barrier and promote the nucleation and growth of the catalytic layer. At the same time, a microcurrent is passed to induce, promoting local oxidation in the interfacial region, increasing the diffusion rate and mobility of grain boundaries, forming a porous structure of the catalytic layer loaded on the substrate (i.e., the conductive substrate), strengthening the connection between the matrix and the catalytic layer, and weakening the stacking of the catalytic layer growth, leaving channels for the discharge of electrolysis bubbles at high current density in the subsequent process.
[0058] The preparation method provided by the present application will be introduced in detail in the form of a complete embodiment as follows, as Figure 2 shown, including:
[0059] The preparation method of the catalytic electrode of the present invention includes steps S201 - S204:
[0060] S201. Pretreatment of the conductive substrate: Select a nickel or nickel-based alloy mesh with 20 - 100 meshes and cut it into 50mm * 50mm; Immerse the cut nickel mesh in an HCl solution to remove surface oxides and roughen it; After taking it out, ultrasonically treat it in ethanol and acetone for 15 minutes respectively, and finally ultrasonically clean it in deionized water and dry it at 60 °C to obtain the treated nickel mesh.
[0061] S202. Preparation of the catalytic precursor solution: Add soluble salts to 100 mL of solvent and stir to dissolve, and configure its concentration to be 0.01 - 5 mol / L. As the precursor for the electrolytic water anode catalyst, nitrates, chlorides, acetates, sulfates, etc. of iron, cobalt, manganese, copper, zinc, chromium, cerium, praseodymium, neodymium, samarium, and gadolinium are preferably used.
[0062] S203. Coating: Uniformly coat the prepared catalytic precursor solution on the surface of the nickel mesh and dry it in air, and repeat the operation 5 - 50 times to make the precursor loading reach 0.5 mg / cm 2 .
[0063] S204. Install in the tank for in-situ growth reaction: After loading the nickel mesh brushed with the catalytic precursor solution into the prefabricated electrolytic cell as the anode, pass a KOH or NaOH electrolyte containing 0.1% growth induction additive into the electrolytic cell, with an electrolyte flow rate of 30 - 100 mL / min per unit electrode area, a mass fraction of 30 wt%, an electrolyte temperature of 40 - 120 °C, and pass a microcurrent with a current density of 0.02 - 20 mA / cm 2 , and continue for 30 minutes.
[0064] The present invention provides an in-situ preparation method for an electrolyzed water hydrogen production catalytic electrode that can be industrially produced in an electrolytic cell. After loading a catalytic precursor solution layer on the surface of a conductive substrate, it is directly placed into the electrolytic cell, and an alkaline electrolyte containing an induced growth additive and a weak current are introduced to synchronously complete the spontaneous growth of the catalytic layer in the cell, obtaining a porous metal hydroxide / hydroxyoxide and oxide catalytic electrode. On the basis of improving the performance of the catalytic electrode, the production difficulty is reduced and the production efficiency is increased. At the same time, a third component is introduced into the basic non-noble metal catalytic active material as a catalytic reaction assistant to adjust the catalytic surface active sites, greatly improving the activity and service life of the electrode.
[0065] The following will prepare catalytic electrodes with multiple examples, and through comparative test data, the excellent performance of the catalytic electrodes prepared by the preparation method of this application will be demonstrated:
[0066] Example 1:
[0067] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5*5 cm, then ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the oxides and oils on the surface. After washing with deionized water and drying at 60 °C, the treated nickel mesh is obtained.
[0068] Weigh 24.24 g of iron(III) nitrate nonahydrate and add it to 100 mL of deionized water, stir to completely dissolve it to obtain a uniformly dispersed catalytic precursor solution. Then use a brush to dip a small amount of the solution and coat it on the surface of the treated nickel mesh, put it into an oven at 80 °C to dry and take it out, then use a brush to dip the catalytic precursor solution and coat it again, and then put it into an oven at 80 °C to dry. Repeat the above operation 20 times. Put the coated electrode (i.e., the conductive substrate treated as above) into a prefabricated electrolytic cell, add 0.1% of 3,4,9,10-perylene tetracarboxylic dianhydride to 30 wt% KOH electrolyte, and introduce it into the electrolytic cell at a rate of 50 mL / min for 30 min. The electrolyte temperature is 80 °C, and the current density is 0.5 mA / cm 2 , obtaining a NiFe2(O)OH-coated nickel electrode.
[0069] Example 2
[0070] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5*5 cm, then ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the oxides and oils on the surface. After washing with deionized water and drying at 60 °C, the treated nickel mesh is obtained.
[0071] Weigh 48.48 g of iron(III) nitrate nonahydrate and add it to 100 mL of deionized water, stir to completely dissolve it to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and coat it on the surface of the treated nickel mesh, place it in an 80 °C oven to dry and then take it out. Then, use a brush to dip the catalytic precursor solution again for coating and place it in an 80 °C oven to dry. Repeat the above operation 20 times. Put the coated electrode into a prefabricated electrolytic cell, add 0.1% of 3,4,9,10-perylene tetracarboxylic dianhydride to 30 wt% KOH electrolyte, and introduce it into the electrolytic cell at a rate of 50 mL / min, with a current density of 0.5 mA / cm 2 , and continue for 30 min, with the electrolyte temperature at 80 °C, to obtain a nickel electrode with a NiFe4(O)OH coating.
[0072] Example 3
[0073] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5 * 5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the surface oxides and oil. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0074] Weigh 11.46 g of iron(II) acetate and add it to 100 mL of deionized water, stir to completely dissolve it to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and coat it on the surface of the treated nickel mesh, place it in an 80 °C oven to dry and then take it out. Then, use a brush to dip the catalytic precursor solution again for coating and place it in an 80 °C oven to dry. Repeat the above operation 20 times. Put the coated electrode into a prefabricated electrolytic cell, add 0.1% of 3,4,9,10-perylene tetracarboxylic dianhydride to 30 wt% KOH electrolyte, and introduce it into the electrolytic cell at a rate of 50 mL / min, with a current density of 0.5 mA / cm 2 , and continue for 30 min, with the electrolyte temperature at 80 °C, to obtain a nickel electrode with a NiFe2(O)OH coating.
[0075] Example 4
[0076] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5 * 5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the surface oxides and oil. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0077] Weigh 17.46 g of cobalt nitrate hexahydrate and add it to 100 mL of deionized water. Stir to completely dissolve it to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and apply it to the surface of the treated nickel mesh. Place it in an oven at 80 °C for drying and then take it out. Again, use a brush to dip the catalytic precursor solution and apply it, and then place it in the oven at 80 °C for drying. Repeat the above operation 20 times. Install the coated electrode into a prefabricated electrolytic cell. Add 0.1% of 3,4,9,10-perylene tetracarboxylic dianhydride to the 30 wt% KOH electrolyte and introduce it into the electrolytic cell at a rate of 50 mL / min. The current density is 0.5 mA / cm 2 , and continue for 30 min. The electrolyte temperature is 80 °C to obtain a nickel electrode with a NiCo2(O)OH coating.
[0078] Example 5
[0079] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5 * 5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min. Then, pretreat the nickel mesh with ethanol and acetone respectively to remove the oxides and oil on the surface. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0080] Weigh 16.16 g of iron nitrate nonahydrate and 5.82 g of cobalt nitrate hexahydrate and add them to 100 mL of deionized water. Stir to completely dissolve them to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and apply it to the surface of the treated nickel mesh. Place it in an oven at 80 °C for drying and then take it out. Again, use a brush to dip the catalytic precursor solution and apply it, and then place it in the oven at 80 °C for drying. Repeat the above operation 20 times. Install the coated electrode into a prefabricated electrolytic cell. Add 0.1% of 3,4,9,10-perylene tetracarboxylic dianhydride to the 30 wt% KOH electrolyte and introduce it into the electrolytic cell at a rate of 50 mL / min. The current density is 0.5 mA / cm 2 , and continue for 30 min. The electrolyte temperature is 80 °C to prepare a ternary NiFe1Co1(O)OH catalytic electrode.
[0081] Example 6
[0082] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5 * 5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min. Then, pretreat the nickel mesh with ethanol and acetone respectively to remove the oxides and oil on the surface. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0083] Weigh 16.16 g of iron(III) nitrate nonahydrate and 5.75 g of zinc sulfate heptahydrate, add them to 100 mL of deionized water, and stir to completely dissolve them to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and coat it on the surface of the treated nickel mesh, place it in an 80 °C oven for drying and then take it out. Then, use a brush to dip the catalytic precursor solution again for coating and place it in an 80 °C oven for drying. Repeat the above operation 20 times. After the coating is completed, install the electrode into a prefabricated electrolytic cell, add 0.1% of 3,4,9,10-perylenetetracarboxylic dianhydride to 30 wt% KOH electrolyte, and introduce it into the electrolytic cell at a rate of 50 mL / min. The current density is 0.5 mA / cm 2 , and continue for 30 min. The electrolyte temperature is 80 °C to prepare a catalytic electrode of ternary NiFe1Zn1(O)OH.
[0084] Example 7
[0085] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5 * 5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the oxides and oil on the surface. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0086] Weigh 16.16 g of iron(III) nitrate nonahydrate and 5.33 g of chromium(III) chloride hexahydrate, add them to 100 mL of deionized water, and stir to completely dissolve them to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and coat it on the surface of the treated nickel mesh, place it in an 80 °C oven for drying and then take it out. Then, use a brush to dip the catalytic precursor solution again for coating and place it in an 80 °C oven for drying. Repeat the above operation 20 times. After the coating is completed, install the electrode into a prefabricated electrolytic cell, add 0.1% of 3,4,9,10-perylenetetracarboxylic dianhydride to 30 wt% KOH electrolyte, and introduce it into the electrolytic cell at a rate of 50 mL / min. The current density is 0.5 mA / cm 2 , and continue for 30 min. The electrolyte temperature is 80 °C to obtain a nickel electrode coated with NiFe1Cr1(O)OH.
[0087] Example 8
[0088] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5 * 5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the oxides and oil on the surface. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0089] Weigh 16.16 g of iron(III) nitrate nonahydrate and 8.68 g of cerium(III) nitrate hexahydrate, add them to 100 mL of deionized water, and stir to completely dissolve them to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and coat it on the surface of the treated nickel mesh. Place it in an 80 °C oven for drying and then take it out. Then, use a brush to dip the catalytic precursor solution again and coat it, and then place it in an 80 °C oven for drying. Repeat the above operation 20 times. Install the coated electrode into a prefabricated electrolytic cell. Add 0.1% of 3,4,9,10-perylenetetracarboxylic dianhydride to the 30 wt% KOH electrolyte and introduce it into the electrolytic cell at a rate of 50 mL / min. The current density is 0.5 mA / cm 2 , and continue for 30 min. The electrolyte temperature is 80 °C to obtain a NiFe1Ce1(O)OH-coated nickel electrode.
[0090] Example 9
[0091] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5*5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the oxides and oil on the surface. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0092] Weigh 16.16 g of iron(III) nitrate nonahydrate and 4.33 g of lanthanum(III) nitrate hexahydrate, add them to 100 mL of deionized water, and stir to completely dissolve them to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and coat it on the surface of the treated nickel mesh. Place it in an 80 °C oven for drying and then take it out. Then, use a brush to dip the catalytic precursor solution again and coat it, and then place it in an 80 °C oven for drying. Repeat the above operation 20 times. Install the coated electrode into a prefabricated electrolytic cell. Add 0.1% of 3,4,9,10-perylenetetracarboxylic dianhydride to the 30 wt% KOH electrolyte and introduce it into the electrolytic cell at a rate of 50 mL / min. The current density is 0.5 mA / cm 2 , and continue for 30 min. The electrolyte temperature is 80 °C to obtain NiFe1La 0。5 (O)OH-coated nickel electrode.
[0093] Example 10
[0094] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5*5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the oxides and oil on the surface. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0095] Weigh 16.16 g of iron(III) nitrate nonahydrate and 0.08 g of samarium(III) nitrate hexahydrate, add them to 100 mL of deionized water, and stir to completely dissolve them to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and coat it on the surface of the treated nickel mesh, place it in an 80 °C oven for drying and then take it out. Then, use the brush to dip the catalytic precursor solution again for coating and place it in an 80 °C oven for drying. Repeat the above operation 20 times. After the coating is completed, install the electrode into a prefabricated electrolytic cell. Add 0.1% of 3,4,9,10-perylene tetracarboxylic dianhydride to 30 wt% KOH electrolyte, and introduce it into the electrolytic cell at a rate of 50 mL / min. The current density is 0.5 mA / cm 2 , and continue for 30 min. The electrolyte temperature is 80 °C to obtain a NiFe1Sm 0.1 (O)OH-coated nickel electrode.
[0096] Comparative Example 1
[0097] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5 * 5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the surface oxides and oils. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0098] Weigh 24.24 g of iron(III) nitrate nonahydrate, add it to 100 mL of deionized water, and stir to completely dissolve it to obtain a uniformly dispersed catalytic precursor solution. Then, use a brush to dip a small amount of the solution and coat it on the surface of the treated nickel mesh, place it in an 80 °C oven for drying and then take it out. Then, use the brush to dip the catalytic precursor solution again for coating and place it in an 80 °C oven for drying. Repeat the above operation 20 times. After the coating is completed, install the electrode into the electrolytic cell, introduce 30 wt% KOH electrolyte at a rate of 50 mL / min, and continue for 30 min. The electrolyte temperature is 80 °C to obtain a NiFe2(O)OH-coated nickel electrode.
[0099] Comparative Example 2
[0100] Cut a 40-mesh nickel mesh into an electrode with geometric dimensions of 5 * 5 cm. Then, ultrasonically treat the nickel mesh with 2 mol / L HCl at 50 °C for 30 min, and then pretreat the nickel mesh with ethanol and acetone respectively to remove the surface oxides and oils. After washing with deionized water, dry it at 60 °C to obtain the treated nickel mesh.
[0101] Some specimens with an area of 10*10 mm were cut from the electrodes obtained in the above Examples 1-5 and Comparative Examples 1 and 2, and tested using the prior art. For example, an electrochemical workstation from Shanghai Chenhua Co., Ltd. was used. Through a three-electrode test method, a platinum sheet was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. The prepared specimen was directly used as the working electrode for testing. Among them, the electrolyte was a 30 wt% NaOH solution, the test environment temperature was controlled at 65 °C, and no iR compensation was performed for all tests.
[0102] And with the test specimen as the anode and the platinum sheet as the cathode, a 30 wt% NaOH solution was used for the accelerated life test at 85 °C in a water bath under the condition of 10 kA / m2 for 20 h.
[0103] The electrodes grown by passing a microcurrent in the electrolytic cell and the electrodes prepared without passing a current in the electrolytic cell were observed using an electron microscope, as Figure 4 and Figure 5 ( Figure 3 for passing a current, Figure 4 for not passing a current). The electrode grown by inducing with a microcurrent has an obvious porous structure, which provides more reaction sites while ensuring the active specific surface area, and is more conducive to the contact reaction between the catalyst and the electrolyte.
[0104] At the same time, the electrode prepared by the preparation method provided in this application directly conducts electrolysis in the in-situ growth electrolytic cell. Using a nickel mesh as the cathode and a 30 wt% NaOH solution as the electrolyte, at 85 °C, a peristaltic pump was used to pump into the cathode chamber and the anode chamber at a circulation rate of 50 mL / min respectively. The electrolysis performance is as Figure 7 and can stably operate for 500 h at a current density of 6 kA / m 2 Among them, the scanning electron microscope image of the NiFe anode after operating for 500 h under the condition of 6 kA / m 2 is as shown in Figure 6 As shown, Figure 8 The test cell voltage is stable at about 2.08 V during operation. Scanning and observing the electrode surface shows no obvious changes, and it still shows a porous flow channel structure with flow channels generated by the introduction of the electrolyte, demonstrating good mechanical stability.
[0105] Table 1 Performance of the electrode after strengthening the test specimen
[0106]
[0107]
[0108] Table 1 shows the test results of the oxygen evolution electrode before and after the above-mentioned strengthening. At 100 mA / cm 2At a given current density, the higher the concentration of the catalytic precursor solution, the lower the overpotential exhibited by the oxygen evolution anode. For the electrodes grown inside and outside the cell, no significant performance differences were shown during the tests. Instead, after strengthening, the performance of the electrodes grown inside the cell was improved, which was due to the further reaction during the strengthening process of the precursor layer electrode caused by the complete wetting of the electrolyte inside the cell. In addition, after introducing a third component element as a catalytic reaction promoter, the electrode performance was further improved. Besides the influence of the synergistic effect, the promoter also had a positive impact on regulating the active sites of the catalyst and enhancing the electrode structure.
[0109] Therefore, in the embodiments of the present application, based on the above test comparison data, the data in each step can be appropriately adjusted to obtain better predictable results.
[0110] Catalytic electrode embodiment:
[0111] The present invention also provides a catalytic electrode, that is, the catalytic electrode prepared by the above preparation method. It should be noted that in this catalytic electrode, the composition of the catalytic layer includes a substance with the general formula NiM x (O)OH; where 0 < x < 5, 0 ≤ y < 5, M is at least one of Mn, Fe, Co, Cu, Mo, and the third component promoter N is Zn, Cr, Ce, La, Pr, Nd, Sm or Gd.
[0112] Regarding the catalytic electrode in the above embodiments, it has been described in detail in the embodiments related to the preparation method, and will not be elaborated here in detail.
[0113] The specific implementation schemes of the catalytic electrode provided by the embodiments of the present application can refer to the implementation manners of the methods in any of the above embodiments, and will not be repeated here.
[0114] It can be understood that the same or similar parts in the above embodiments can be referred to each other, and the content not detailed in some embodiments can be referred to the same or similar content in other embodiments.
[0115] It should be noted that in the description of the present invention, the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance. In addition, in the description of the present invention, unless otherwise specified, the meaning of "a plurality" refers to at least two.
[0116] Any process or method description depicted in the flowchart or described otherwise herein can be understood to represent a module, segment, or portion of code including one or more executable instructions for implementing a specific logical function or process. The scope of the preferred embodiments of the present invention includes additional implementations where functions may be executed not in the order shown or discussed, including in a substantially simultaneous manner according to the relevant functions or in a reverse order, which should be understood by those skilled in the art to which the embodiments of the present invention pertain.
[0117] It should be understood that various parts of the present invention can be implemented by hardware, software, firmware, or a combination thereof. In the above embodiments, multiple steps or methods can be implemented by software or firmware stored in a memory and executed by a suitable instruction execution system. For example, if implemented by hardware, as in another embodiment, any one or a combination of the following techniques well known in the art can be used: discrete logic circuits with logic gate circuits for implementing logical functions on data signals, application specific integrated circuits with appropriate combinational logic gate circuits, programmable gate arrays (PGAs), field programmable gate arrays (FPGAs), etc.
[0118] Those of ordinary skill in the art of the present technology can understand that all or part of the steps carried by the method of implementing the above embodiments can be completed by instructing relevant hardware through a program. The said program can be stored in a computer-readable storage medium. When the program is executed, it includes one or a combination of the steps of the method embodiments.
[0119] In addition, in each embodiment of the present invention, the functional units can be integrated into a processing module, or each unit can exist physically alone, or two or more units can be integrated into a module. The above integrated module can be implemented in the form of hardware or in the form of a software functional module. When the above integrated module is implemented in the form of a software functional module and sold or used as an independent product, it can also be stored in a computer-readable storage medium.
[0120] The above-mentioned storage medium can be a read-only memory, a magnetic disk, an optical disc, etc.
[0121] In the description of this specification, descriptions with reference to terms such as "one embodiment", "some embodiments", "example", "specific example", or "some examples", etc. mean that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.
[0122] Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those of ordinary skill in the art can make changes, modifications, substitutions, and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a catalytic electrode, characterized in that: include: Using an acidic catalyst precursor solution, a catalyst precursor layer is formed on the surface of a preset conductive substrate; placing a conductive substrate with a catalytic precursor layer into a prefabricated electrolytic cell; A high-temperature alkaline electrolyte containing a growth-inducing additive and a microcurrent are introduced into the prefabricated electrolytic cell to react, induce growth and activate, so as to directionally generate a porous catalytic layer with flow channels on a conductive substrate with a catalytic precursor layer. Deionized water is introduced into the prefabricated electrolytic cell to clean the catalytic electrode, thereby obtaining a catalytic electrode.
2. The method for preparing a catalytic electrode according to claim 1, characterized in that: The method of forming a catalytic precursor layer on a surface of a preset conductive substrate using an acidic catalytic precursor solution comprises: Uniformly coating an acidic catalytic precursor solution on the surface of the preset conductive substrate and performing a drying process; The coating and drying processes are repeated sequentially until the weight of the catalytic precursor layer on the surface of the preset conductive substrate reaches the target value, and the minimum target value is 0.2 mg / cm 2 .
3. The method for preparing a catalytic electrode according to claim 1, characterized in that: The step of placing the conductive substrate with the catalytic precursor layer into the prefabricated electrolytic cell comprises: placing the conductive substrate with the catalytic precursor layer into the anode chamber of the prefabricated electrolytic cell.
4. The method for preparing a catalytic electrode according to claim 1, characterized in that: The material of the conductive substrate includes at least one of nickel and a nickel-based alloy.
5. The method for preparing a catalytic electrode according to claim 1, characterized in that: The catalytic precursor solution includes a solution formed by dissolving one or more of nitrates, sulfates, chlorides and acetates of a target non-precious metal in an acidic solvent; wherein the target non-precious metal includes at least one of nickel, cobalt, iron, manganese and copper; and a third component, wherein the third component includes at least one of zinc, chromium, cerium, praseodymium, neodymium, samarium and gadolinium.
6. The method for preparing a catalytic electrode according to claim 1, characterized in that: The alkaline electrolyte of the growth-inducing additive includes a KOH or NaOH electrolyte with a concentration of 20%-30%, a temperature of 40-120° C., and the time for passing the alkaline electrolyte is 30 minutes; the growth-inducing additive is one of 3,4,9,10-perylenetetracarboxylic dianhydride, 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene and purified terephthalic acid.
7. The method for preparing a catalytic electrode according to claim 1, characterized in that: The current density of the current passed is 0.02-20 mA / cm 2 , and the duration of passing the current is 30 minutes.
8. The method for preparing a catalytic electrode according to claim 1, characterized in that: Before forming a catalytic precursor layer on the surface of a preset conductive substrate using an acidic catalytic precursor solution, the method further includes: Immersing the conductive substrate in an HCl solution for ultrasonic or sandblasting treatment; Then, the conductive substrate after ultrasonic or sandblasting treatment is ultrasonically treated in ethanol and acetone in sequence; Finally, the conductive substrate after ultrasonic treatment in acetone was washed with deionized water and dried.
9. A catalytic electrode, characterized in that: The catalytic electrode is prepared by the method for preparing the catalytic electrode as described in any one of claims 1 to 8.
10. The catalytic electrode according to claim 9, characterized in that The components of the catalytic layer of the catalytic electrode include one or more of oxides, hydroxides, and oxyhydroxides; The general formula of the composition of the catalyst layer is NiM x N y (O)OH substances; Among them, 0<x<5, 0≤y<5, the catalytic component M is at least one of Mn, Fe, Co, Cu, and Mo, and the third component additive N is at least one of Zn, Cr, Ce, La, Pr, Nd, Sm or Gd.
Citation Information
Patent Citations
Method for producing an electrode for electrolysis
CN104937142B
Electrolyzed water catalyst and preparation method thereof
CN113802130A
Electrolyzed water catalysis net and preparation method thereof
CN114774967A